2018
DOI: 10.1186/s12939-018-0734-z
|View full text |Cite
|
Sign up to set email alerts
|

The impact of nursing students on the health-related quality of life and perceived social support of a rural population in Ecuador: effects of a service-based learning course

Abstract: BackgroundStudents seeking degrees in healthcare in Ecuador participate in community improvement projects and provide free health services under the supervision of faculty health professionals. The aim of this study is to determine the impact of a community-based intervention delivered by nursing students on health-related quality of life (HRQoL) and perceived social support of a rural population in Ecuador.MethodsA quasi-experimental non-equivalent control group design study was conducted in two rural communi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 28 publications
0
9
0
1
Order By: Relevance
“…This is supported by a study in the USA where it was found that physiologic indices like rest and sleep when satisfied, can enhance the quality of life of students. Further, it was suggested in the study that promoting the importance of a quality sleep pattern maybe enhance their sense of well-being and general quality of life as students (Walcott et al, 2018). This finding was supported by the study of Oztasan et al (2016) that when the quality of life is low and unsatisfying for students, the mental symptoms increase.…”
Section: Discussionmentioning
confidence: 82%
“…This is supported by a study in the USA where it was found that physiologic indices like rest and sleep when satisfied, can enhance the quality of life of students. Further, it was suggested in the study that promoting the importance of a quality sleep pattern maybe enhance their sense of well-being and general quality of life as students (Walcott et al, 2018). This finding was supported by the study of Oztasan et al (2016) that when the quality of life is low and unsatisfying for students, the mental symptoms increase.…”
Section: Discussionmentioning
confidence: 82%
“…In the two quality of life studies, in which no specific health conditions were described, interventions were provided by physical therapy students in a clinic setting 49 or nursing students undertaking home visits. 25 In both cases, significant improvements in physical quality of life ratings were observed, with no significant changes found in other areas of health quality of life.…”
Section: Resultsmentioning
confidence: 89%
“…Most studies were conducted in the United States with the exceptions of two studies of outcomes from SRCs in Australia 22 , 23 and one in each of the United Kingdom, c Ecuador, 25 and Canada. 26 The most common study method used were case reviews (n = 34) either in the context of a pre-post or a cohort study design.…”
Section: Resultsmentioning
confidence: 99%
“…Differences in patterns of change between the two groups resulted in the experimental group having significantly better physical health than the control group at the end of the intervention. Social support interventions have been shown to positively affect physical health ( Walcott et al, 2018 ). Support from relatives and friends may also moderate the negative effects of secondary traumatic stress on physical health ( Fu et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, no study has examined the effect of social support on ProQOL. A social support intervention was found to significantly improve the physical health but not the mental health of nursing students at the end of the intervention ( Walcott et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%